2004
DOI: 10.1021/bc034118r
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptide Semicarbazide Glass Slide Microarrays: Characterization and Comparison with Amine Slides in Serodetection Studies

Abstract: We have described in the accompanying article the preparation of peptide-protein semicarbazide microarrays and their use for the simultaneous serodetection of antibodies directed against different pathogens. Here, we present a comparative study between semicarbazide and amine glass slides in an immunofluorescent serodetection assay using HIV (Gp120, Gp41), HCV (mix-HCV, core, NS3, and NS4), and HBV (HBs) recombinant antigens. Amine and semicarbazide surfaces displayed the same sensitivity for antibodies detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…Positive and negative ion spectra were internally calibrated using H + , H 2 + , CH 3 + , C 2 H 2 + , C 3 H 5 + and H − , C − , CH − , C 2 H − , and C 4 H − peaks, respectively. The total ion dose was less than 1.0×10 [12] ions/cm 2 [2] and well below the static limit of SIMS (∼1.0×10 [13] ions/cm 2 [2]). Effective charge compensation for samples on glass slides was obtained by using a pulsed electron flood gun.…”
Section: Time-of-flight Secondary Ion Mass Spectrometrymentioning
confidence: 92%
See 1 more Smart Citation
“…Positive and negative ion spectra were internally calibrated using H + , H 2 + , CH 3 + , C 2 H 2 + , C 3 H 5 + and H − , C − , CH − , C 2 H − , and C 4 H − peaks, respectively. The total ion dose was less than 1.0×10 [12] ions/cm 2 [2] and well below the static limit of SIMS (∼1.0×10 [13] ions/cm 2 [2]). Effective charge compensation for samples on glass slides was obtained by using a pulsed electron flood gun.…”
Section: Time-of-flight Secondary Ion Mass Spectrometrymentioning
confidence: 92%
“…Ageing influences technologically important parameters as morphology, wettability, and stability expressed as reactivity to, e.g., proteins [11][12][13]. Usually, users of amine slides store them for several days to months prior to use under rather different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[56] The same group also constructed protein microarrays in which proteins were adsorbed onto the semicarbazide-modified surfaces, and they analyzed interactions with HIV (gp120, gp41), HCV (mix-HCV, core, NS3, and NS4), and HBV (HBs) recombinant antigens. [157] Meanwhile, immunoglobulin E (IgE) epitope mapping of food allergens is a prerequisite for engineering hypoallergenic immunotherapeutic agents and can provide important information regarding a patient's immune response. Schreffler et al developed an immunoassay based on a peptide microarray to map peanut epitopes.…”
Section: Peptide Microarraysmentioning
confidence: 99%
“…To minimize the disadvantages, various chemical surfaces on glass slides were tested with a number of coupling chemistries, such as amine (Duburcq et al, 2004a), aldehyde (Zammatteo et al, 2000), poly-l-lysine (Haab et al, 2001), epoxy , agarose (Afanassiev et al, 2000), polyacrylamide (Angenendt et al, 2002) and nitrocellulose (Qiu et al, 2004). It is reported that polyacrylamide slides showed a sixfold signal-to-noise ratio higher than poly-l-lysine slides coated with an additional photo-reactive crosslinker (HSAB slides) when applied to protein profiling of prostate cancer (Miller et al, 2003).…”
Section: Introductionmentioning
confidence: 99%